Being with care: dance practice in times of ecosocial crisis - Ojanen, Wilhelmina (Taideyliopiston Teatterikorkeakoulu, 2022)
This thesis aims to examine how dance practice can provide a way of being with care. The research methodology focuses on how one can develop a caring relationship with other worlds through dance practice. The main research question is: What does “being with care” mean in a time of ecosocial crisis, and how can it be fostered through dance practice? In this thesis, the term dance practice encompasses the act of movement, the dancing itself, and the choreographic, pedagogical, and improvisational moving-thinking one engages with others. The theoretical frameworks that support this thesis are from the fields of contemporary feminist, political and phenomenological studies on care ethics, embodied care, and embodiment. This research focuses on care from ecological, philosophical, and pedagogical perspectives and understands care as something that exists not only in human relations but also as a responsible and reciprocal way of living with morethan- human worlds. This thesis analyses the artistic process of the site-specific dance piece becoming-with and the dance pedagogue-researcher’s embodied experience of how care was present in the artistic practice. becoming-with is a dance piece about the intertwined and co-evolving relationship between human and more-than-human worlds. becoming-with was created by choreographer Wilhelmina Ojanen, performers Hanna Kahrola, Janina Salmela, Wilma Seppälä and Kardo Shiwan, musician Tapani Rinne, lighting designer and technician Jaakko Sirainen and costume and space designer Mirei Kato, together with the more-than-human worlds involved in the piece. The work premiered 17th of December 2021 at Kenneli D.I.Y indoor skate pool in Hiedanranta, Tampere, and was presented twice more on the 18th and 19th of December 2021. The artistic practice of becoming-with unfolded over two months and encompassed spending time together in the studio reading, conversing, dancing, and working with different materials. Through improvisational dance and somatic practices that invoked the imagination and invited deeper sensing of the world around oneself, we sought to explore what becoming-with meant for each of us. In this thesis, the artistic practice of becoming-with is analysed through elements present during the process: The unknown, The senses: touch, Thinking-together to become otherwise, and Materiality and responsibility. The practice of writing poems was used as an artistic method of inquiry into the process. The analysis of the theoretical background and the analysis of the artistic process produced the results of this artistic research as four guiding principles of being with care. These are embodiment, imagination, attentiveness, and responsibility. The four guiding principles are intertwined and ultimately propose being with care as a way of approaching living and creating in times of ecosocial crisis. The guiding principles of being with care will be further defined and developed in my future work as a choreographer and dance educator.
Keywords: Care; Dance practice; Dance pedagogy; Somatics; Embodiment; Ecosocial crisis; Climate crisis; More than human; Becoming-with; Thinking together; Becoming otherwise; Corporeality; Dance; Improvisation in dance; Environmental responsibility; Artistic Research; Imagination; tanssi; improvisointi; ympäristöarvot; mielikuvitus; taiteellinen tutkimus; pedagogiikka; ilmastokriisi; fi=tanssinopettaja|sv=danspedagogik|en=Dance Pedagogy|